Konsep Negara, Tujuan Negara, dan Urgensi Dasar Negara - Siti Fatimah Mustari; Imah Yulianti; Nabila Zahara; Riska Mulyana; Bambang Trisno (International Forum of Researchers and Lecturers, 2024)
This research discusses in depth the concept of the state, the goals of the state, and the basic urgency of the state. The concept of the state includes the meaning, constituent elements, and role of the state in people's lives. The goals of the state are explored through various perspectives, ranging from security goals to societal welfare. Next, the basic urgency of the state is outlined by highlighting the importance of a strong philosophical and constitutional foundation in shaping state identity and policies. This study emphasizes that a comprehensive understanding of the concepts, goals and foundations of the state is very important to maintain the stability and progress of a country. Through theoretical analysis and literature review, this research provides critical insights for policy makers and academics in efforts to strengthen the country's foundations.